PENGARUH KERAPATAN TANAMAN DAN JENIS PUPUK TERHADAP PERTUMBUHAN DAN PRODUKSI HIJAUAN RATUN SORGUM (Sorghum bicolor (L.) Moench): Effect of Plant Density and Type of Fertilizer on Growth and Forage Production of Ratoon Sorghum (Sorghum Bicolor (L.) Moench - Renaldy Alimuddin; Budiman Nohong; Rinduwati Rinduwati (Departemen Nutrisi dan Makanan Ternak, Fakultas Peternakan, Universitas Hasanuddin, 2021)
Sorghum (Sorghum bicolor (L.) Moench) is a type of cereal plant that has the potential to be cultivated and developed as a source of forage for ruminants. One of the efforts to increase sorghum production is through the use of the ratoon system accompanied by the application of organic and inorganic fertilizers. This study aims to determine the effect of plant density and type of fertilizer on the growth and production of sorghum ratoon (Sorghum bicolor(L.) Moench).This study used a completely randomized design (CRD) with a factorial pattern consisting of 2 factors and 3 treatments with 3 (three) replicates each, namely The First Factor K2 = 2 plants/polybag, The Second Factor K3 = 3 plants/polybag, and P1 = 200 g bokashi/polybag (40 tons/ha), P2 = 4.58 g NPK/polybag (329 kg NPK/ha) P3 = bokashi + 2.29 g NPK/polybag. Based on the results of the study, it was concluded that the highest plant was found in the K2P2 treatment, which was 236.33 cm, the highest leaf growth rate in the K2P1 treatment was 7.16 strands and the highest dry matter production level in the K2P2 treatment was 52.5 grams. This means that the type of fertilizer that has a source of N is very necessary for the growth of ratoon sorghum plants. Keywords : Bokashi, Density, Fertilizer, Growth, Production and Sorghum Ratoon